2020
DOI: 10.1007/s10668-020-00849-0
|View full text |Cite
|
Sign up to set email alerts
|

Understanding COVID-19 transmission through Bayesian probabilistic modeling and GIS-based Voronoi approach: a policy perspective

Abstract: Originating from Wuhan, China, COVID-19 is spreading rapidly throughout the world. The transmission rate is reported to be high for this novel strain of coronavirus, called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), as compared to its predecessors. Major strategies in terms of clinical trials of medicines and vaccines, social distancing, use of personal protective equipment (PPE), and so on are being implemented in order to control the spread. The current study concentrates on lockdown and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 42 publications
1
66
0
2
Order By: Relevance
“…This demonstrates the importance of implementing prevention measures before the fast growth region in order to delay the spread of the virus. Recent studies in India show similar conclusions ( Bherwani et al, 2020 ). On the other hand, countries in Asia vary in T D and I CR due to the way the pandemic evolved in that continent, since it showed first in China, South Korea, and Japan, and much later in the southern region.…”
Section: Resultssupporting
confidence: 73%
“…This demonstrates the importance of implementing prevention measures before the fast growth region in order to delay the spread of the virus. Recent studies in India show similar conclusions ( Bherwani et al, 2020 ). On the other hand, countries in Asia vary in T D and I CR due to the way the pandemic evolved in that continent, since it showed first in China, South Korea, and Japan, and much later in the southern region.…”
Section: Resultssupporting
confidence: 73%
“…Mumbai has the highest population density and has the highest COVID-19 cases. Bherwani et al (2020) also reported that the western region of Maharashtra which has a high population has recorded high COVID-19 confirmed cases, while the south region which has low population has evidently reported low infected cases. A similar picture was reported from Algeria (Kadi and Khelfaoui 2020), Turkey (Şahin 2020;Coşkun et al 2020), Wuhan city of China (Pansini and Fornacca 2020), the US state and some Europian countries (Babbitt et al 2020) where their population density creates the potential for higher person-to-person contagion rate, thus the higher rate of spread of this virus.…”
Section: Relationship Between Demographic Factors Air Pollutions Anmentioning
confidence: 91%
“…Thiessen Polygons are created from a set of feature points, therefore, every individual polygon specifies an effect area around its input feature point (Wheeler et al 2010 ). Therefore, Thiessen Polygon uses the basic method of analysing neighborhood and proximity (Bherwani et al 2020a , b ). In this study, Thiessen Polygons were prepared separately for population density and COVID-19 positive cases for each state for understanding the significance of correlation.…”
Section: Methodsmentioning
confidence: 99%
“…In the context of COVID-19, statistical spatial models examined the widespread infection rate in India. Model studies have also been used to understand the risk assessment of COVID-19 spread in different regions (Bherwani et al 2020a , b ; Das et al 2020 ; Gupta et al 2020 ). However, the correlation analysis for the different variables in the COVID-19 data series is an important aspect.…”
Section: Introductionmentioning
confidence: 99%